THE PROFILE OF JUNIOR HIGH SCHOOL STUDENTS’ PROBLEM SOLVING IN ANSWERING THE CONTENT PISA TEST OF UNCERTAINTY AND DATA BASED ON IDEAL PROBLEM SOLVING - Damayanti, Erlina Rahma; Yunianta, Tri Nova Hasti (MaPan : Jurnal Matematika dan Pembelajaran, 2018)
Abstract: The study aims to find out the profile of junior high school students’ problem solving in answering the content PISA test of uncertainty and data based on IDEAL (I-Identify problem, D-Define goal, E-Explore possible strategies, A-Anticipate outcomes and act, and L-Look back and learn) problem solving. Three students of the third grade state junior high school (SMPN) 1 Salatiga of academic year 2018/2019 were selected as the subjects of this study. The study used test, interview, and documentation as data collection techniques. Based on the results of the written test and interview, it is found that some students were able to implement all problem solving stages appropriately and sequentially. The subjects tended to ignore ’exploring strategies’ and ’look and learning’ stages. Abstrak: Penelitian ini bertujuan untuk mengetahui profil pemecahan masalah siswa dalam menyelesaikan soal PISA konten uncertainty and data berdasarkan pemecahan masalah IDEAL (I-Identidy problem, D-Define goal, E-Explore possible strategies, A-Anticipate outcomes and act, dan L-Look back and learn). Jenis penelitian ini adalah penelitian kualitatif. Subjek dalam penelitian ini adalah 3 siswa kelas VIII SMP Negeri 1 Salatiga tahun pelajaran 2018/2019. Teknik pengumpulan data yang digunakan adalah tes, wawancara, dan dokumentasi. Berdasarkan hasil tes tertulis dan wawancara diperolehbahwa sebagian siswa mampu melaksanakan tahapan pemecahan masalah dengan runtut dan tepat, dan cenderung semua subjek kurang dalam tahap explore strategies dan look and learning.